SPEAKING GRADUATE STUDENT FOR PERSONAL BRANDING AND EMPLOYMENT OPPORTUNITIES - SILALAHI, ELFRIDA BR.; Tanabara, Agnes G; Wene, Imelda Woa (Fakultas Keguruan dan Ilmu Pendidikan, Universitas HKBP Nommensen, 2023)
This is certainly very useful considering the importance of having the ability to speak English. Research methodology of this research is descriptive qualitative methods. The data was taken from student’s observation and interview. This research explains how important English communication is to improve personal branding for better job opportunities and heaving ability to speak English will provide better and wider job opportunities. The resulting of this research is students communicating optimally lead a person to better job opportunities that proved form students observation and interviewing those students get better job opportunities. Communication can be in the form of oral or written, English is chosen as the language used in the world of work. Personal branding is a factor that already exists in every individual; it is formed differently depending on the surrounding environment. Where personal branding is correlated with the communication made and the process will later be used. The purpose of building personal branding is to gain the trust of people around us for our credibility. In the current era of growing globalization, the role of communication is becoming increasingly vital.